Derechos y obligaciones derivadas de la unión marital de hecho (2001)
As the humanity evolves, the right must adapt its regulations in parallel with this evolution. This way every state in particular, he has had to organize a norms system to regulate social facts of big significance and juridical transcendency. The coexistence of a man and a woman is a need for natural and biological order, and it can go over to this union by means of rites, ceremony, civil or religious acts, or for the simple fact of the union without fulfilling any formality. This informal union called of diverse nature in the course of the juridical history of the world, is what before the law 54 of 1990, was named a Concubinage in our legislation This denomination, of for itself shameful, was adding in the long run list of denigrating names that was granted to this type of unions and that in its historical moment were concubinages, cohabitations, barraganias, etc., 54 of 1.990 was changed into the marital union really established and recognized by the law The legislative footpath that the informal unions have had to face to obtain its legal recognition, has been rough and desert. But, with the expedition of the law earlier written down and the promulgation of the political constitution of 1.991, a legal frame has been obtained so that it is possible to do justice opposite to a fact of undeniable hereditary and social consequences.